PEMANFAATAN ABU PENGASAPAN KOPRA PADA TANAMAN BAYAM (Amaranthus sp) - Mandagi, Vanessa; Sumayku, Bertje R.A; Pamandungan, Yefta; Paulus, Jeanne M.; Sompotan, Saartje; Tulung, Stella M.T. (EUGENIA, 2024)
Spinach (Amaranthus sp) is a plant belonging to the Amaranthaceae family. Spinach is one of the oldest food plants in the world originating from America, which has been cultivated around 6700 years BC and is now spread throughout tropical and subtropical areas throughout the world. Copra fumigation ash contains macro and micro nutrients that plants need, one of which is potassium. This research aims to determine the effect of copra fumigation ash on the growth of spinach plants. This research was carried out at the Green House, Faculty of Agriculture, Sam Ratulangi University, Manado, North Sulawesi from June to July 2024. This research used a Randomized Group Design (RAK) with six treatments and four replications consisting of Without Ash Copra Fumigation (K0), 5 tons Copra Fumigation Ash/ha (K1), 10 tonnes of Copra Fumigation Ash/ha (K2), 15 tonnes of Copra Fumigation Ash/ha (K3), 20 tonnes of Copra Fumigation Ash/ha (K4) and 25 tonnes of Copra Fumigation Ash/ha ( K5). The research data were analyzed using the F test using the Microsoft Office Excel program to determine the effect of copra fumigation ash treatment on the growth of spinach plants. The research results showed that copra fumigation ash had a significant effect on the variable height of spinach plants but not on the number of leaves and width of spinach leaves. Copra fumigation ash also has a very significant effect on the fresh weight of spinach plants. It is recommended to use copra ash at a dose of 20 tons/ha as the recommended dose for spinach cultivation activities.